THE DIFFERENT MENTAL HEALTH PATIENT QUALITY OF LIFE DURING SHACKLING, TREATMENT, AND POST TREATMENT - Widodo, Arif; Supratman, Supratman (Universitas Ahmad Dahlan (UAD), 2020)
Background: Mental health is a well-being mental state associated with happiness, joy, satisfaction, achievement, optimism, and hope. Good mental health allows a harmonious and productive life as an integral part of one's quality of life by taking into account all aspects of human life. This study aims to assess the different quality of life among mental health disorder patients during shackling, treatment, and post-treatment in Sukoharjo Regency.Methods: Quantitative descriptive was used in this study. Our population was all mental disorder patient in Sukoharjo District who has experienced with shackling and finished the treatment in the RSJD “dr Arif Zainudin,